Towards high-quality development: The complex role of environmental regulation - Jie Li; Xuguang Wang (PLoS ONE, 2025)
High-quality development is a necessary condition for a healthy society, and environmental regulation is an important means to maintain high-quality development. Against this backdrop, this study takes the Yellow River Basin in China as an example to explore the complex impact of environmental regulation on high-quality economic development, with a particular focus on the indirect impact of regional pollution heterogeneity on the complex influence. Utilizing panel data from 2011 to 2022, this paper constructs an evaluation index system for the Yellow River Basin’s high-quality development that encompasses 29 fundamental indicators and applies the Entropy-Weighted TOPSIS method for a comprehensive assessment. The research found a significant positive relationship between environmental regulation and high-quality economic development, confirming the key role of environmental regulation in balancing economic growth and environmental protection. The article further analyzes the complex impact of environmental regulation under the background of pollution heterogeneity and discovers the nonlinear and threshold effect characteristics between environmental regulation and high-quality development. Notably, the positive influence of environmental regulation on high-quality economic development is already evident at lower intensities, yet becomes markedly more pronounced when the regulatory intensity reaches or exceeds a certain threshold. Additionally, the paper delves into the heterogeneous impacts of environmental regulation on high-quality economic development across regions with differing pollution levels. The findings indicate that in regions of severe pollution, the positive effect of environmental regulation is considerably more pronounced, potentially attributable to the heightened public concern for environmental issues and the stringent environmental protection measures implemented by the government. The study also addresses the issue of endogeneity using instrumental variable methods to ensure the robustness of the results. Ultimately, the paper presents targeted policy recommendations, including the formulation of region-specific environmental regulations, the establishment of regional collaborative governance mechanisms, the enhancement of public participation and oversight, and the promotion of green technological innovation, all aimed at fostering the coordinated advancement of high-quality economic development and environmental protection in the Yellow River Basin.